2013
DOI: 10.1186/1936-6434-6-23
|View full text |Cite
|
Sign up to set email alerts
|

Examining the evolution education literature with a focus on teachers: major findings, goals for teacher preparation, and directions for future research

Abstract: The theory of evolution is the fundamental backbone to the discipline of biology, yet many students possess misunderstandings. The teacher is the most important school-based factor in student learning, and therefore to improve students' understandings of evolution, we must better prepare teachers. The purpose of this paper is three-fold. First, we reviewed empirical research studies focused on K-12 teachers regarding evolution education from 1993 to 2011 with the purpose of identifying major themes of research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 77 publications
4
46
0
8
Order By: Relevance
“…What students are taught in high school influences their acceptance of evolution and what they believe should be taught to future generations in high school (Table 4). In a review of empirical research studies on K-12 teachers regarding evolution, Sickel and Friedrichsen (2013) show that there are profound misconceptions about evolution that color how teachers present the topic and how much time they devote to evolution. The factor most often associated with a rejection of evolution is strength of religious convictions (Losh and Nzekwe 2011a,b;Sickel and Friedrichsen 2013;Trani 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What students are taught in high school influences their acceptance of evolution and what they believe should be taught to future generations in high school (Table 4). In a review of empirical research studies on K-12 teachers regarding evolution, Sickel and Friedrichsen (2013) show that there are profound misconceptions about evolution that color how teachers present the topic and how much time they devote to evolution. The factor most often associated with a rejection of evolution is strength of religious convictions (Losh and Nzekwe 2011a,b;Sickel and Friedrichsen 2013;Trani 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a review of empirical research studies on K-12 teachers regarding evolution, Sickel and Friedrichsen (2013) show that there are profound misconceptions about evolution that color how teachers present the topic and how much time they devote to evolution. The factor most often associated with a rejection of evolution is strength of religious convictions (Losh and Nzekwe 2011a,b;Sickel and Friedrichsen 2013;Trani 2004). For example, a recent study of women (n = 375 females) in teacher education courses found that 93% who view the Bible as the literal word of God also reject evolution, while 80% of those that view the Bible as a book of legends accept evolution (Levesque and Guillaume 2010).…”
Section: Discussionmentioning
confidence: 99%
“…First, teachers will present evolution as "just a theory" (Asghar et al, 2007;Berkman & Plutzer, 2015;Miller, 2008), implying that theories are less robust than other scientific knowledge. Second, even more troubling is the willingness some teachers have to include non-scientific explanations alongside evolutionary theory (Berkman & Plutzer, 2011;Blank & Anderson, 1997;Sickel & Friedrichsen, 2013).…”
Section: Results Of Controversy = Softening Evolution or Including Crementioning
confidence: 99%
“…These PSTs completed a course that successfully incorporated instruction that emphasized NOS as suggested by the literature (Bloom & Weinburgh, 2007;Lombrozo et al, 2008;Sickel & Friedrichsen, 2013). Yet, our results seem to suggest that despite being exposed to this type of instruction, their understandings of science may not develop sufficiently to make informed decisions about specific, socioscientific issues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation